HUBUNGAN PENGETAHUAN DAN SIKAP IBU TERHADAP PERAWATAN BALITA DENGAN ISPA - Cici Fitria Ulandari; Arneliwati " "; Gamya Tri Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Toddlerhood is a time when the body at risk for a disease, one of them is Acute Respiratory Tract Infections (ARTI). The role of parents, especially mothers are necessary to prevent ARTI in toddler, knowledge and attitudes of mothers about ARTI become a determinant for mothers to treat toddler with ARTI. This study aimed to determine the relationship of the level of knowledge and attitudes of mothers towards toddler with ARTI treatment at Puskesmas Harapan Raya Pekanbaru. The study consisted of 73 samples with non-probability sampling techniques and analysis by chi square test. The results showed no relationship between the level of knowledge to the treatment of toddler with ARTI p value = (0.001) < (0.05), and there are relationship attitude towards the treatment of toddler with ARTI p value = (0,047) < (0.05). Based on the results, suggested to mothers who have toddler with ARTI to increase knowledge about ARTI. Keyword: Acute respiratory tract infections, mother attitudes, mother knowledge,treatment.